Left atrial phasic transport function closely correlates with fibrotic and arrhythmogenic atrial tissue degeneration in atrial fibrillation patients: cardiac magnetic resonance feature tracking and voltage mapping. Issue 9 (9th March 2021) - Schönbauer, Robert; Tomala, Jakub; Kirstein, Bettina; Huo, Yan; Gaspar, Thomas; Richter, Utz; Piorkowski, Judith; Schönbauer, Marie-Sophie; Fiedler, Lukas; Roithinger, Franz Xaver; Hengstenberg, Christian; Mascherbauer, Julia; et al.
Abstract: Aims: To characterize the association of phasic left atrial (LA) transport function and LA fibrosis guided by multimodality imaging containing cardiac magnetic resonance imaging (CMR) feature tracking and bipolar voltage mapping. Methods and results: Consecutive patients presenting for first-time ablation of atrial fibrillation (AF) were prospectively enrolled. Each patient underwent CMR prior to the ablation procedure. LA phasic indexed volumes (LA-Vi) and emptying fractions (LA-EF) were calculated and CMR feature tracking guided LA wall motion analysis was performed. LA bipolar voltage mapping was carried out in sinus rhythm to find areas of low voltage as a surrogate for fibrosis and arrhythmogenesis. One hundred and sixty-eight patients were enrolled. Low-voltage areas (LVAs) were present in 70 patients (42%). Contrary to LA volume, CMR based LA-EF [odds ratio (OR) 0.88, 95% confidence interval (CI) 0.80–0.96, P = 0.005] and LA booster pump strain rate (SR) (OR 0.98, 95% CI 0.97–0.99, P = 0.001) significantly predicted presence and extent of LVA in multivariate logistic regression analysis for patients scanned in SR. In receiver operating characteristic analysis, LA-EF <40% carried a sensitivity of 83% and specificity of 76% (area under the curve 0.8; 95% CI 0.71–0.89) to predict presence of LVA. For patients scanned in AF only minimal LA-Vi on CMR (OR: 1.06; 95% CI: 1.02–1.10; P = 0.002) predicted presence of LVA. Conclusion: For patients scanned in SR LA-EF and LA booster pump SR are closely linked to the presence and extent of LA LVA. Graphical Abstract: